Prince of stories the many worlds of Neil Gaiman - Wagner, Hank; Golden, Christopher; Bissette, Stephen (St. Martin's Press, 2008)
Chronicles the history and impact of the complete works of Gaiman in film, fiction, music, comic books, and beyond.
Includes bibliographical references
Keywords: Gaiman, Neil -- Handbooks, manuals, etc; Gaiman, Neil -- Stories, plots, etc; Gaiman, Neil -- Characters; Gaiman, Neil -- 1960-